Dosimetric Evaluation of Incidental Irradiation to the Internal Mammary Chain After Surgery in Breast Cancer Patients - Wang, Wei; Sun, Tao; Meng, Yingtao; Xu, Min; Zhang, Yingjie; Shao, Qian; Song, Yuanfang; Li, Jianbin (Frontiers in Oncology, 2022)
Background and Purpose The low rate of internal mammary node (IMN) recurrence was attributed to systemic therapy and internal mammary chain (IMC) coverage by the tangential fields of irradiation. This study aimed to evaluate the incidental irradiation dose to the IMC in breast cancer patients after surgery and to estimate the clinical predictive parameters affecting the magnitude of the IMC. Materials and Methods A total of 138 patients treated with postmastectomy radiotherapy and 210 patients undergoing radiotherapy after breast-conserving surgery (BCS) in our hospital were retrospectively analyzed. The mean dose (Dmean) to the IMC and the first to third intercostal spaces of IMC levels (ICS1–3) were evaluated. We evaluated the IMC coverage according to the type of surgery and whether the ipsilateral supraclavicular fossa (SCF) was included in the irradiation field. Results The incidental radiation dose to the IMC was 29.69 Gy, and the dose delivered to the IMC, ICS1, and ICS2 showed a greater coverage in the modified radical mastectomy (MRM) group when compared with the BCS group (32.85 vs. 27.1 Gy, 26.6 vs. 12.5 Gy, 34.63 vs. 30.42 Gy). The dose delivered to ICS3 showed no difference between the MRM and BCS groups (37.41 vs. 36.24 Gy). Furthermore, 131 patients (37.64%) received radiotherapy to the chest wall and ipsilateral SCF. In the univariate analysis, both surgery type and SCF irradiation were parameters affecting the Dmean of incidental radiation to the IMC (r = −0.179, P = 0.001; r = −0.175, P = 0.001). In the multivariate analysis, surgery type was the only correlative factor that affected incidental radiation dose to the IMC (r = –3.534, P = 0.000). Conclusion The real influencing factor of incidental dose to the IMC was the surgery form rather than the accession of SCF irradiation.